ECONOMIC EMPOWERMENT OF PESANTREN AND ITS IMPACT ON COMMUNITY WELFARE IN RAJAPOLAH, TASIKMALAYA: A CIBEST MODEL APPROACH - Milah, Joharul; Nasrulloh, Agus Ahmad; Friantoro, Dian (Al-Infaq: Jurnal Ekonomi Islam, 2024)
This study aims to determine the impact of economic empowerment program of islamic boarding school or pesantren through the procurement of the Laundry business unit of Pesantren Darussalam in Rajapolah Tasikmalaya by measuring community welfare after participating in the the Pesantren economic empowerment program. The research method used is descriptive quantitative using the CIBEST Model which measures the level of material and spiritual welfare of the community. The data collection technique in this study used a questionnaire with a sample size of 39 people who had participated in the DN Laundry business unit program. The results showed that the economic empowerment of Pesantren Darussalam Rajapolah Tasikmalaya through the DN Laundry business unit program can increase community income and spirituality. This shows that the DN Laundry business unit program is the right empowerment program to have a positive impact on improving community welfare.